Molecular characterization and phylogenetic analysis of major envelope protein gene (B2L) and ATPase protein gene (A32L) of orf virus isolates from goats in Southern, Thailand - Wongkae Watjiranon; Chya Vannakovida; Thanidtha Te-Chaniyom; Natakorn Nokchan; Syriam Sooksawasdi Na Ayudhya (PLoS ONE, 2026)
Orf virus (ORFV), a member of the Poxviridae family, causes contagious ecthyma (CE), a viral skin disease in small ruminants. Due to its self-limiting nature, low mortality rate and economic consequences, CE is considered as a neglected disease, resulting in underreporting in Thailand. Despite its global presence, the genetic characterization of ORFV in Thailand, especially in the southern region where there is high density of goat farming, is largely unknown. To address the knowledge gap, we conducted genetic and evolutionary analysis including phylogenetic, BEAST, and discriminant analysis of principal components (DAPC), on ORFV isolated from Southern Thailand, utilizing conserved B2L gene (major envelope protein) and A32L gene (C-terminal ATPase protein). All suspected CE meat goats across 2 farms in Songkhla and Pattani provinces in 2024 tested ORFV positive via PCR using ORFV-specific primers. These isolates along with a positive control isolate (Pattani 2020) were used for molecular characterization and genetic analysis. The 2024 isolates clustered with Malaysian strains based on phylogenetic and population analysis. BEAST analysis of these isolates further indicated a shared evolutionary origin around 2007, suggesting transboundary spread. Although the 2024 isolates were highly related, some differentiation observed for both genes and they evolved separately from 2020 Pattani isolate suggesting ongoing local evolution and genetic variation in the regional population. Moreover, the Pattani 2020 isolate was phylogenetically distinct and revealed a distinct ancestral origin, suggesting a separate introduction event into the region. Notably, heterogeneity in C-terminal region of ATPase gene was observed, including 4 amino acid deletions in Songkhla 2024 and Pattani 2020 isolates, and unique substitutions (G258S and G260S) in Pattani 2024 which may cause a distinct cluster based on DAPC analysis. Collectively, our findings indicate diverse ORFV evolution in Southern Thailand, necessitating continued molecular surveillance and genetic characterization to improve national control strategies.